Spiritual Hajj in the time of pandemic - Muhsin, Sayyed Mohamed (IslamiCity, 2021)
Since physically many can’t undertake a journey to the holiest city this year, it compels us to think of a spiritual trip to Makkah only to try our best to reap the benefits of hajj, as part of seeing opportunities in tribulations and attempting possibly finest replacements. For that, let’s do a ‘hajj’ through the implications of the hajj, navigating its maqāṣid (higher objectives of Sharīʿah in enjoining the hajj) and spiritually circling around the Kaʿbah.